2014
DOI: 10.7555/jbr.27.20130051
|View full text |Cite
|
Sign up to set email alerts
|

A new free-hand pedicle screw placement technique with reference to the supraspinal ligament

Abstract: We sought to compare the safety and accuracy of a new free-hand pedicle screw placement technique to that of the conventional technique. One hundred fifty-three consecutive adult patients with simple fracture in the thoracic or/and lumbar spine were alternately assigned to either the new free-hand or the conventional group. In the new free-hand technique group, preoperative computerized tomography (CT) images were used to calculate the targeted medial-lateral angle of each pedicle trajectory and the pedicle sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 28 publications
(23 reference statements)
0
15
0
Order By: Relevance
“…Accurate PS placement in C7 is critical for stabilizing the vertebral segments. Among the three screw types (lateral mass screw, laminar screw, and PS), PS has been recognized as a superior option for posterior stabilization due to its high degree of strength, which can endure segmental motion [ 1 2 11 ]. Several experimental and clinical studies have demonstrated that PS screws can provide more strength for de-stabilized cervical segments compared with other screws [ 1 3 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Accurate PS placement in C7 is critical for stabilizing the vertebral segments. Among the three screw types (lateral mass screw, laminar screw, and PS), PS has been recognized as a superior option for posterior stabilization due to its high degree of strength, which can endure segmental motion [ 1 2 11 ]. Several experimental and clinical studies have demonstrated that PS screws can provide more strength for de-stabilized cervical segments compared with other screws [ 1 3 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Posterior stabilization procedures with screw-rod systems are frequently used to treat various cervical pathologies in the cervical spine including cervical stenosis, segmental instability, and fracture-dislocation [ 1 2 3 4 5 ]. In the cervical spine, placement of a posterior screw requires a lateral mass screw, laminar screw, and a pedicle screw (PS).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations